2018
DOI: 10.3389/fvets.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Aujeszky’s Disease and Hepatitis E Viruses Transmission between Domestic Pigs and Wild Boars in Corsica: Evaluating the Importance of Wild/Domestic Interactions and the Efficacy of Management Measures

Abstract: Wildlife species as reservoirs of infectious pathogens represent a serious constraint in the implementation of disease management strategies. In the Mediterranean island of Corsica, the dynamics of hepatitis E virus (HEV) and Aujeszky’s disease virus (ADV) are suspected to be influenced by interactions between wild and domestic pigs. To improve our understanding of these influences, we first compared the seroprevalences of both viruses in domestic pig populations from different locations with contrasted levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(146 citation statements)
references
References 40 publications
5
139
1
1
Order By: Relevance
“…Concurrently, the agricultural decline and abandonment of agricultural land in recent decades have led to a notable increase in wild boar populations as evidenced by the approximately 30,000 wild boars hunted annually (ONCFS, ). Similar to other Mediterranean locations, these conditions provide an ideal environment for the interaction between wild and domestic pig populations (Jori, Relun et al., ) and the subsequent maintenance and transmission of pathogens detrimental for both the pig industry (Albina et al., ; Mur et al., ) and human health (Charrier et al., ; Pavio et al., ; Richomme, Boschiroli, Hars, Casabianca, & Ducrot, ). Previous work developed to collect information on interactions between wild and domestic pigs among farmers and hunters indicated a high incidence of direct contacts in extensive pig farms.…”
Section: Discussionmentioning
confidence: 97%
“…Concurrently, the agricultural decline and abandonment of agricultural land in recent decades have led to a notable increase in wild boar populations as evidenced by the approximately 30,000 wild boars hunted annually (ONCFS, ). Similar to other Mediterranean locations, these conditions provide an ideal environment for the interaction between wild and domestic pig populations (Jori, Relun et al., ) and the subsequent maintenance and transmission of pathogens detrimental for both the pig industry (Albina et al., ; Mur et al., ) and human health (Charrier et al., ; Pavio et al., ; Richomme, Boschiroli, Hars, Casabianca, & Ducrot, ). Previous work developed to collect information on interactions between wild and domestic pigs among farmers and hunters indicated a high incidence of direct contacts in extensive pig farms.…”
Section: Discussionmentioning
confidence: 97%
“…In Corsica, traditional extensive (or semi‐extensive) outdoor pig farming system is common. This kind of farming facilitates contact with wild boar populations sharing pathogens such as HEV (Charrier et al, ; Jori et al, ). Only 10% of Corsican pork products come from this traditional sector.…”
Section: Introductionmentioning
confidence: 99%
“…Two major studies on HEV have already been carried out on domestic pigs in Corsica. These were seroprevalence studies and anti‐HEV IgG has been detected in domestic and wild boar populations (Charrier et al, ; Jori et al, ). The higher seroprevalence observed in Corsican domestic pigs (88%), compared with Corsican wild boars (29%) suggests a spillover of HEV from domestic pigs to wild boars (Charrier et al, ; Jori et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serological surveys indicated that PRV was still circulating in wild boars, with prevalence levels reaching 20-50% in regions with the highest population density [16,17], especially in the north-east and center of mainland France, as well as in Corsica [17][18][19]. The risk of such endemic PR in wild boars lies in reintroducing PRV into pig herds, especially those on outdoor farms due to potential contact between domestic pigs and wild boars [20]. Indeed, since the end of the eradication program in the pig industry, three PR outbreaks were detected through serological analyses in open-air pig farms in 2010, 2018, and 2019 [21][22][23].…”
Section: Introductionmentioning
confidence: 99%